Recent trends in the epidemiology, diagnosis, treatment, and mechanisms of resistance in clinical Aspergillus species: A general review with a special focus on the Middle Eastern and North African region - Ayate Zakaria; Marwan Osman; Fouad Dabboussi; Rayane Rafei; Hassan Mallat; Nicolas Papon; Jean-Philippe Bouchara; Monzer Hamze (Elsevier, 2020)
Globally, more than billion people suffer from fungal infections each year. The early diagnosis of aspergillosis is mandatory for successful treatment outcome. As careful testing takes time, epidemiological surveillance is crucial to guide individual patient therapy and to promote a high standard of health care. In this paper, we first present current trends in the epidemiology and antifungal susceptibility patterns of Aspergillus spp. in Middle Eastern and North African (MENA) countries in order to support infectious disease specialists and health workforces in this geographic area to treat adequately patients with aspergillosis. Then we discuss the existing literature data regarding the available diagnostic tools and antifungal resistance mechanisms of Aspergillus spp. Although a limited number of studies were reviewed here, the currently available data show that Aspergillus infections are not negligible in the MENA region, and that the emergence of antifungal resistance is a growing health issue, especially among immunocompromised patients. Keywords: Aspergillus spp., Epidemiology, Antifungal resistance, Molecular mechanisms, MENA region